Hadith Analysis Silent Treatment Psychological Perspective (Abraham H Maslow Theory Review) - Alda Nihayatul A’rifah; Budi Ichwayudi; Nadiatul Maziyyah Attarwiyah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The existence of a problem in a relationship is unavoidable. It is a consequence of an interaction between individuals. Communication is essential for each individual, through communication a person can convey their thoughts and feelings appropriately. Good communication between individuals is one of the many efforts to minimize and solve problems. Some cases found that when getting a problem, many people actually choose to be silent and ignore related parties rather than communicate. They think that silence is an alternative in solving problems, but in fact, silence is not helpful, it will cause new problems and make the situation more complicated, this attitude is called silent treatment. The research presents three comprehensive points about silent treatment, namely the hadiths that discuss silent treatment, in this case the author focuses on the hadith in Sunan al-Tirmidhī number 1855, silent treatment from a psychological perspective using Abraham H Maslow's hierarchy of needs theory and the correlation between the two. Descriptive qualitative research is the method used in this study. This method focuses on studying a problem in depth.